Electrical properties of semiconductor structures with Si nanoclusters in SiO₂ grown by high temperature annealing technology of SiOx layer, X<2 - Bunak, S.V.; Buyanin, A.A.; Ilchenko, V.V.; Marin, V.V.; Melnik, V.P.; Khacevich, I.M.; Tretyak, O.V.; Shkavro, A.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The theoretical and experimental investigations of electrical properties of the SiO₂/Si-ncs/SiO₂/Si structures grown by high temperature annealing SiOx, X<2, have been carried out. The influence of Si cluster growth conditions on frequency dependences of C - V characteristics, static and dynamic conductance of investigated structures has been clearly observed. As a result of theoretical modeling, C - V dependences have been calculated. The experimentally obtained negative constituent of differential capacitance has been qualitatively described. It has been experimentally found that the SiO₂/Si-ncs/SiO₂/Si structures with the tunnel dielectric layer revealed the effect of memorizing.